2022
DOI: 10.1002/admt.202270081
|View full text |Cite
|
Sign up to set email alerts
|

Polydopamine and Magnesium Ions Loaded 3D‐Printed Ti‐6Al‐4V Implants Coating with Enhanced Osteogenesis and Antibacterial Abilities (Adv. Mater. Technol. 12/2022)

Abstract: Multi‐Scale Composite Structures In article number 2200598, Zhenbing Ji, Yi Wan, Chao Liu, and co‐workers prepare a 3D‐printed Ti‐6Al‐4V implant with osteogenic induction and antibacterial properties. Multi‐scale composite structures and bioactive coatings constructed on the implant surface by acid etching, anodic oxidation, and hydrothermal treatment show excellent ability to improve the rate of bone integration and antibacterial effect compared with the unmodified implant surface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Previous study reported that magnesium ion could effectively reduce the adhesion of bacteria as well as destroy the structure of bacteria, and the surface containing magnesium ions also had obvious antibacterial effect on suspended bacteria in solution. [ 70 ] Magnesium ions are believed to react with cardiolipin in the cell membrane of Gram‐positive bacteria, which changes the cell membrane and makes the bacteria more vulnerable. [ 71 ] Magnesium‐based antibacterial agents are considered to penetrate into bacterial cell membranes, inhibit bacterial growth, and finally damage bacteria.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous study reported that magnesium ion could effectively reduce the adhesion of bacteria as well as destroy the structure of bacteria, and the surface containing magnesium ions also had obvious antibacterial effect on suspended bacteria in solution. [ 70 ] Magnesium ions are believed to react with cardiolipin in the cell membrane of Gram‐positive bacteria, which changes the cell membrane and makes the bacteria more vulnerable. [ 71 ] Magnesium‐based antibacterial agents are considered to penetrate into bacterial cell membranes, inhibit bacterial growth, and finally damage bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…[ 72 ] However, the antibacterial mechanism of magnesium ion remains controversial and needs further study. [ 70 ]…”
Section: Resultsmentioning
confidence: 99%